Preferential School Subsidy In Chile: Focused Decentralization For School Improvement - Cristian Oyarzún (Global Writing Academica Researching and Publishing, 2023)
This article reflects on the decentralization processes promoted in Chilean school education through the creation of a subsidy focused on low socioeconomic groups, called the Preferential School Subsidy (SEP). To that end, this public policy is illustrated by means of a Logical Framework approach and results from the period 2009-2016 corresponding to municipal schools of two communes attached to the SEP are reviewed. The work derives in two conjectures. First, this subsidy would not be inducing improvements in academic performance, despite the sustained increase in resources. Secondly, there is an increasing concentration of priority students in the contexts analyzed, which agrees with the marked school segregation observed in Chile.